2020
DOI: 10.1093/cid/ciaa1134
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Granulocyte Telomeres Among Children and Adolescents With Perinatally Acquired Human Immunodeficiency Virus Infection and Chronic Lung Disease in Zimbabwe

Abstract: Background Chronic lung disease (CLD) has been reported among African children with perinatally-acquired HIV infection (C-PHIV), despite combination antiretroviral therapy (cART). In adults, shorter telomere length (TL) has been reported in association with both CLD and HIV. As little is known in children, our objective was to compare TL in HIV+ (cART-naïve or treated) and HIV-negative children with and without CLD. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The BREATHE trial was a multicountry trial conducted in Zimbabwe and Malawi, and the findings were reported in two manuscripts 14,15 . Six papers reported two cohorts in Zimbabwe: ZENITH cohort of ART‐naïve HIV‐positive children and INHALE cohort of ART‐established children 17–22 . Three cohorts were in South Africa, including two earlier cohorts in 2012 and 2015, 27,28 and the more recent Cape Town Adolescent Antiretroviral Cohort (CTAAC), which was summarised in four papers 6,23–25 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The BREATHE trial was a multicountry trial conducted in Zimbabwe and Malawi, and the findings were reported in two manuscripts 14,15 . Six papers reported two cohorts in Zimbabwe: ZENITH cohort of ART‐naïve HIV‐positive children and INHALE cohort of ART‐established children 17–22 . Three cohorts were in South Africa, including two earlier cohorts in 2012 and 2015, 27,28 and the more recent Cape Town Adolescent Antiretroviral Cohort (CTAAC), which was summarised in four papers 6,23–25 .…”
Section: Resultsmentioning
confidence: 99%
“…Twelve papers enrolled participants established on ART 6,10,14,15,18–25 and six papers enrolled participants regardless of their ART status with the percentage on ART ranging from 69% to 97% 5,11–13,26,28 . Three papers did not report ART prevalence 16,17,27 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations